CMIP5 Climate Models Overestimate Cooling by Volcanic Aerosols. Issue 3 (3rd February 2020) - Chylek, Petr; Folland, Chris; Klett, James D.; Dubey, Manvendra K.
Abstract: We compare projections of the observed hemispherical mean surface temperature (HadCRUT4.6.0.0) and the ensemble mean of CMIP5 climate models' simulations on a set of standard regression model forcing variables. We find that the volcanic aerosol regression coefficients of the CMIP5 simulations are consistently significantly larger (by 40–49%) than the volcanic aerosol coefficients of the observed temperature. The probability that the observed differences are caused just by chance is much less than 0.01. The overestimate is due to the climate models' response to volcanic aerosol radiative forcing. The largest overestimate occurs in the winter season of each hemisphere. We hypothesize that the models' parameterization of aerosol‐cloud interactions within ice and mixed phase clouds is a likely source of this discrepancy. Furthermore, the models significantly underestimate the effect of solar variability on temperature for both hemispheres. Plain Language Summary: We compare the observed and climate models' simulated hemispherical mean temperature projections on a set of influencing factors. The influencing factors include the man‐made greenhouse gases and aerosols as well as natural solar variability, volcanic eruptions, and internal climate variability. If the observed and model‐simulated temperatures were the same, the projections would be very similar. We find that the projections are not similar. The climate models overestimate the cooling effect of volcanic activity and underestimate the effect of the variability of solar radiation. Our results point out that future models should improve the treatment of volcanic aerosols and solar variability to increase the reliability of climate change projections. Key Points: Regression analysis independently confirms that climate models overestimate the cooling effect of volcanic aerosols The overestimated volcanic cooling is caused by models' response to volcanic aerosol forcing, not by the error in the forcing The models also significantly underestimate the effect of solar variability on mean global and hemispheric temperature